LANTANUM COMPLEXASI STUDY WITH MAKROSIKLIS COMPOUND AND CHARACTERIZATION AS SELECTIVE ELECTRONIC ION LANTANUM - Suyanta Suyanta; Sunarto Sunarto; Lis Permana Sari (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2011)
The aim of this research are (1) to study the complexation constant of La(III) ion by N,N’-dikarboksimetildiaza-18-crown-6 ligant with difference concentration of KNO3, and (2) to study the lanthanum (III) ion selective electrode (La-ISE) potential response which follows the Nernst equation. The characters of the electrode studied are: response time, life time, detection limit, dynamic range and selectivity. The complexation constant of La(III) ion by N,N’- dikarboksimetildiaza-18-crown-6 ligant are finded by potentiometry titration with 0.0005 M, 0.001 M, dan 0.005 M KNO3 supported electrolite. The titration are doing by 0.00794 M KOH until pH 7. The result of constant complexation (Kf) La(III) ion with N,N’-dikarboksimetildiaza-18-crown-6 difference KNO3 0.005 M, 0.001 M, dan 0.005 M simultaniuesly are 101,02 , 101,12, dan 101,32. The electrode had a response time of 27.14 ± 4.79 seconds and could be used for 50 days. The linear range was between 10-5 M to 10-1 M and the detection limit is 3.92x10-6 M.